Managing Major Life Changes: An Exploratory Study Using the Bridges Transitions Framework to Help Foster Youth Prepare for Discharge - Ande A. Nesmith (Children)
Background: Adolescents in foster care endure frequent disruptive transitions, often culminating in discharge to independent living rather than reunification or adoption. Former foster youth fare poorly once on their own, with high rates of homelessness and social disconnection. This study explored the use of the Bridges Transitions Framework near the end of placement to help youth cope with the transition to adulthood. Methods: In this exploratory study, the framework was integrated into a foster agency’s programming; then, we assessed outcomes using administrative data and youth interviews. Thirty-five youth participated. Status of employment, education, and social support was collected 18 months after exposure to the framework. Results: The participants reported moderate to high levels of social support, which is often limited or absent among foster care leavers. Relative to rates reported in state-level foster care data, participants had substantially higher rates of school enrollment after discharge. With very few empirically assessed models available for this population that specifically address internal coping with such substantial life changes, the Transitions Framework offers a tool that may help foster youth navigate aging out of care. Securing lasting and meaningful social support and employment and completing education remain elusive for former foster youth. Conclusions: To confirm the utility of the Transitions Framework, it is recommended to assess it with a large sample and matched comparison group over time.